Gasification and Techno-Economic Study of Palm Shell Biomass and the Utilization of Dual Fuel Diesel Engine Operated Diesel Engine - Hasman Hasan Suli; Bambang Sudarmanta (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Indonesia's oil reserves and production are steadily declining, accompanied by increasing fossil fuel consumption, particularly in Diesel Power Plants, which contribute to environmental impacts and exacerbate global warming. In response, the government issued a policy in 2028 to implement carbon emission trading for Diesel Power Plants with a capacity below 2 MW, as part of Indonesia's commitment to achieving Net Zero Emission (NZE) by 2060. Considering the significant state assets in the form of diesel-powered generators (approximately 5,200 diesel power plants) still operating throughout Indonesia, the government has also issued policies and strategic plans to develop Biomass Power Plants. This research focuses on examining the combination of biosolar B35 and syngas usage in diesel engines, known as dual fuel engine technology, utilizing abundant palm shell biomass waste in Southeast Sulawesi. The gasification process to create syngas uses a multi-stage downdraft gasifier system with the optimal air ratio variation from previous research, namely 1:7:2 in the pyrolysis, oxidation, and reduction zones. Testing is conducted on a diesel engine at 3000 rpm with load variations ranging from 500 Watt to 4500 Watt. The load is gradually increased at 500-Watt intervals. The syngas mass flow rate is also varied by adjusting four different syngas valve openings to the diesel engine's intake manifold. This study will compare the results of diesel engine operation using single fuel (biosolar B35) with dual fuel (biosolar B35 + syngas) at each engine load interval to determine engine performance, biosolar B35 fuel substitution or savings, carbon reduction in the dual fuel diesel system, and calculate the techno-economics for up-scaling on a 250 kW capacity engine at PT Nusantara Power, Unit Pembangkitan Kendari, ULPLTD Kolaka, Southeast Sulawesi. The aim is to support government programs and policies in realizing environmentally friendly and sustainable Diesel Power Plants, as well as to open opportunities for developing biomass-based dual fuel engine technology in Indonesia.